The original spellings of Thryothorus Vieillot, 1816 (Vertebrata, Aves): a correction - David, Normand; Dubois, Alain (Zootaxa, 2011)
While discussing the problems related to multiple original spellings or symprotographs (Dubois 2010: 14) of nomina in zootaxonomy, David et al. (2009: 5) stated that one of the generic bird nomina created by Vieillot (1816) had been so under two different spellings: Thriothorus (p. 45) and Thryothorus (p. 70). They pointed to the fact that subsequently Vieillot (1819: 55) had only used the spelling Thryothorus for this nomen, and thus had acted as a first-reviser between the two spellings under the new Rule introduced in Article 24.2.4 of the last edition of the Code (Anonymous 1999), a nomenclatural act designated by Dubois (2010: 15) as an internal first-reviser action or IFRA.